Comparison of the Performance of Cryptocurrency Bitcoin and Stock as an Alternative Investment - Shabrina Herawati; Kurniawan Arif Maspul; Heri Sasono; I Gusti Ngurah Agung Dewantara Putra; Muhammad Syafri; Raúl Eleazar Arias Sánchez (ProBisnis : Jurnal Manajemen, 2023)
The research aims to test whether there is a real difference between the investment performance of bitcoin and other investment instruments, namely shares. This research is quantitative research. The unit of analysis in this research is the monthly closing price of bitcoin and LQ45 shares for the period January 2018 to April 2021, namely 80 pieces of data. The analytical method used is the comparative method and the data used is secondary data. The results of this research show that there is no real difference between bitcoin and LQ45 shares when viewed from returns, there is a real difference between bitcoin and LQ45 shares when viewed from risk, there is a real difference between bitcoin and LQ45 shares when viewed from Sharpe performance measures. When making an investment, pay close attention to the returns and risks of both bitcoin and shares, don't be tempted by the potential profits without knowing the various risks that could occur and spreading assets across several investment instruments is one of the things recommended by this research.